Surgical treatment of the patient with compound odontoma located in the mandible - a case report - Osica, Piotr; Osica, Karolina; Janas-Naze, Anna (Journal of Education, Health and Sport, 2017)
The article describes case of a 20-year-old patient who had been treated surgically due to compound odontoma of the mandible in the area of teeth 32- 34.